On the real performance of groundwater heat pumps: Experimental evidence from a residential district. (25th June 2021) - Biglia, Alessandro; Ferrara, Maria; Fabrizio, Enrico
Highlights: Heat pump is a key clean energy technology for residential buildings. Monitoring and data analysis is key to optimize system integration and operation. Real performance of groundwater multipurpose heat pumps is lower than expected. Improvements to the heat pumps design and control logic are proposed and validated. Systematic approach for system data collection and analysis is needed. Abstract: Heat pumps are among the most promising technologies driving energy transitions towards the carbon reduction objectives. Their use is being particularly encouraged in the residential sector, where the heating and cooling uses account for the larger energy demand. However, their real performance often does not correspond to designers' expectations, leading to higher running energy costs than expected, and the reasons should be primarily investigated by means of large data collection and analysis. This paper reports the results of a long-term monitoring campaign of a multipurpose groundwater heat pump system for a district of multifamily buildings in Italy. The survey includes data on thermal energy consumption for space heating, domestic hot water, space cooling and electricity consumption of the groundwater heat pumps taken between 2017 and 2018. It was shown that the performance of the installed groundwater heat pumps was significantly lower (up to 60%) than expected. Some defined strategies, mainly related to the system control logic, were demonstrated to be able to significantly increase the system performance, highlighting the need for improvements in integrated design and control strategies since the early design phase and for continuous monitoring in operation to optimise the system integration in real contexts.